A Systematic Review of BIM Adoption and Implementation Challenges in Design & Build Contracts: Insights and Implications for Nepal - Mishra, Suman Kumar; Ayob, Mohamad; Ibrahim, Nurazim (Journal of Advanced Academic Research, 2026)
The design & build (D&B) projects can be made efficient, cost-effective, and quality-assured throughBuilding Information Modeling (BIM). Its adoption is limited in developing countries. The paper is aPRISMA-based systematic review of 21 empirical and conceptual studies on the topic published between2000 and 2025. The review investigates obstacles to BIM adoption as far as Nepal is concerned. Eachstudy was treated as a qualitative case and therefore, a thematic analysis was carried out. Codes weredetermined and sorted into major themes. There were five significant obstacles, namely technical,organizational, financial, contractual, and policy or cultural. All situations had common technical andorganizational barriers. There were greater financial, contractual, and policy-related impediments in thedeveloping countries. Low industry maturity, high cost, fragmented practices, unclear contracts, and lesssupport for regulations are some of the reasons that limit BIM adoption in Nepal. The results demonstratethe necessity of national BIM standards, capacity building, financial incentives, contractual reforms, andincreased awareness of the stakeholders. The presented research offers evidence-based information to helpenhance the implementation of BIM and achieve better cost, time, and quality results in resource-limitedsituations.